Application of Principles of Philosophy of Science in Improving the Effectiveness of Education Management in Madrasah Aliyah Fathur Rahman Batu Sopang - Hifni, Hifni; Wardhana, Kautsar Eka (Poltanesa, 2023)
This research aims to elucidate and critically assess the application of principles outlined in the Philosophy of Science as a foundational framework to enhance the efficacy of educational management at Madrasah Aliyah Fathur Rahman Batu Sopang. Positioned as a comprehensive paradigm, the Philosophy of Science serves as a guiding compass and philosophical underpinning for educational development within the confines of the mentioned madrasa. Utilizing a qualitative research approach with a case study design, the study employs in-depth interviews, observational techniques, and document analysis as principal methods of data collection. The findings reveal how the intrinsic principles of the Philosophy of Science, including objectivity, the scientific method, and the nexus between knowledge and reality, are assimilated and operationalized across diverse facets of educational management within Madrasah Aliyah Fathur Rahman. The analytical framework also examines responses and the consequential impact of applying these principles on overall educational management effectiveness, encompassing leadership dynamics, decision-making processes, and enhancements in pedagogical quality and the learning environment. The application of the philosophy of science and the principles of Islamic education creates a robust foundation for the development of a holistic and effective educational system. Implementing the philosophy of science, with a focus on objectivity, scientific methods, and the interconnectedness between knowledge and reality, provides a profound philosophical basis for the learning process. These principles align with Islamic values that emphasize the importance of knowledge, justice, and the harmony between reason and revelation. Through the integration of the philosophy of science in Islamic education, the learning process can become more rational, purposeful, and responsive to the spiritual and intellectual needs of students. Thus, the application of the philosophy of science can assist in formulating teaching methods and managing Islamic education that is not only based on faith but also utilizes scientific principles to achieve a deeper and sustainable understanding.